Litigio estratégico en el marco del trabajo clínico en derechos humanos: a propósito del Proyecto Urbano Cinturón Verde Metropolitano (2017)
Since 2004 the city of Medellín has been presenting a series of urban changes that respond to the model of social urbanism. One of these works of urban development is the Metropolitan Green Belt, whose main purpose is to control the urban expansion of the city, proposed in the name of public interest and executed by the Administration of Aníbal Gaviria (2012-2015), under Commitments of equity and improvement of the quality of life of citizens from social inclusion. This project has generated tensions with the population of Commune 8, which he says will benefit, because of the relocations necessary to materialize it and for the minimal participation that the community has had in the territory intervention plan, The Green Belt. The methodology used is the case study, which through the systematization of experiences is presented as the possibility to reflect on issues such as: the role of legal clinics with a social approach in the training of lawyers, city models and the Social costs involved in development projects, tensions between human rights and urban development. In that sense, it is hoped to address these issues, from a human rights perspective. The most important conclusions invite us to think of systematic, integral and interdisciplinary actions from the social and human sciences that respond effectively to the needs of the people. In addition to considering the legal clinic as a valuable training possibility for strategic litigation.